Formation of the innovative culture as a factor of modernization of modern society (Journal of Philosophy Culture and Political Science, 2018)
The essence of the phenomenon of innovation and its role in the modernization of society and culture are considered in the article. The authors consider the nature of innovative culture and social innovations. In the article the authors reveal their role and significance in the conditions of modernization of modern society. The authors give characteristics of innovative content in some spheres of public life. The article presents theoretical and methodological approaches to the study of innovative culture. The article reveals the influence of innovation culture on human development. It is shown how an innovative culture influences the improvement of the qualities and abilities of a person. The authors analyze the cultural functions of innovation. The article analyzes innovations as an element of the social system. The authors show innovation as a criterion for the development of modern society.Key words: society, culture, education, science, values, creativity, modernization, innovations, globalization, instability, sustainability.